Design and Monitoring Automatization Of Exhaust Fan Through Smartphone at PT Semen Tonasa - Pance Asyik; Eko Hadi Nugroho (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
Pfister coal feeder is an important piece of equipment in the development of the cement industry at PT Semen Tonasa, which if damage occurs will cause production to stop and result in losses. The pfister control panel is easily damaged at temperatures above 40oC. Because of that, an air conditioner was installed, the dusty factory conditions caused an AC error and delayed repairs resulting in a trip pfister coal feeder. To anticipate all of this, it is necessary to monitor factory temperature, so an exhaust fan is installed which can circulate clean air and remove dirty air. In addition to maintaining the temperature of the control panel so that it does not increase. PLC Allen Bradley helps to monitor temperature, which can be accessed via a smartphone so that temperature monitoring can be done anywhere. The research method used in this study is mixed research, which combines qualitative and quantitative research, in which the research design is based on assumptions as well as research. The results of this study are to use the Microsoft Windows 2000 operating system and RS link to produce images and exhaust fan automation to prevent coal feeder trip pfister due to high temperatures is to monitor via a smartphone to monitor the function of existing tools.